A Randomized Trial of Convalescent Plasma in Covid-19 Severe Pneumonia - Simonovich, Ventura A. (2020)
BACKGROUND:Convalescent plasma is frequently administered to patients with Covid-19 and hasbeen reported, largely on the basis of observational data, to improve clinical outcomes.Minimal data are available from adequately powered randomized, controlled trials. METHODS:We randomly assigned hospitalized adult patients with severe Covid-19 pneumoniain a 2:1 ratio to receive convalescent plasma or placebo. The primary outcome wasthe patient?s clinical status 30 days after the intervention, as measured on a six-pointordinal scale ranging from total recovery to death. RESULTS:A total of 228 patients were assigned to receive convalescent plasma and 105 toreceive placebo. The median time from the onset of symptoms to enrollment inthe trial was 8 days (interquartile range, 5 to 10), and hypoxemia was the mostfrequent severity criterion for enrollment. The infused convalescent plasma had amedian titer of 1:3200 of total SARS-CoV-2 antibodies (interquartile range, 1:800 to1:3200]. No patients were lost to follow-up. At day 30 day, no significant differencewas noted between the convalescent plasma group and the placebo group in thedistribution of clinical outcomes according to the ordinal scale (odds ratio, 0.83(95% confidence interval [CI], 0.52 to 1.35; P=0.46). Overall mortality was 10.96%in the convalescent plasma group and 11.43% in the placebo group, for a risk difference of −0.46 percentage points (95% CI, −7.8 to 6.8). Total SARS-CoV-2 antibodytiters tended to be higher in the convalescent plasma group at day 2 after the intervention. Adverse events and serious adverse events were similar in the two groups. CONCLUSIONS:no significant differences were observed in clinical status or overall mortality between patients treated with convalescent plasma and those who received placebo.(PlasmAr ClinicalTrials.gov number, NCT04383535.)